Impact of welding steel rod rotor bars on ripple mill efficiency and cost-effectiveness at Sumatera Jaya Agro Lestari Sawit Coconut Plant - Lubis, Sudirman; Pane, Rafsanzani; Siregar, Irpansyah (Politeknik Negeri Lhokseumawe, 2023)
PT. Sumatera Jaya Agro Lestari is an industry that is moving in the field of Coke Processing, some long processes that include Loading Ramp, Sterilizer,Trheser, Digester, Pressing, Clarification, and Kernel Plant stations, some problems that occur in the kernel stations mainly to Efficiency results on the Ripple Mill machine, not out of the Operation and Maintenance Standards performed by Using the achievement of the target of the Cernel by the efficiency standard of 96%, on Ripple mill machines often occur cworn outes on Stell Rod due to the input of the ripple Mill Too Over Load, and the amount of nut less mature, for that was done a study on Stel Rod that has already Worn out by performing the Rewelding Method, i.e. the addition of the meat of the steel Rod to 5 mm of the surface of the Rotor-Disc to obtain the maximum Effectiveness result. The steel rod is the most important part of the mill ripple machine consisting of stone mills that move automatically so that it will not reach the maximum efficiency result at mill mills ripple rod. With the welding method, the surface of the welded meat is applied to a steel rod with a thickness of 5mm to 7mm using the MWH 500 type electrode to form the return of the base of the new steel rods surface where the strength of the electrodes and the formation of the surface are correct. The results can be inferred from the efficiency of the impact of welding steel Rod averages 93.38% achieving a very high efficiency.